2020
DOI: 10.3390/ijerph17196953
|View full text |Cite
|
Sign up to set email alerts
|

The Recommended and Excessive Preventive Behaviors during the COVID-19 Pandemic: A Community-Based Online Survey in China

Abstract: COVID-19 presents unprecedented challenges to the global public health response. Preventive behaviors and keeping social distance are regarded as compelling ways to prevent COVID-19. This study focused on the sociological and psychological factors associated with proper and excessive preventive behaviors of the COVID-19 outbreak in China. For the sample, we collected the data of 4788 participants who were surveyed between 4 April and 15 April 2020 from eight provinces in China. This study designed a self-fille… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 48 publications
1
24
1
Order By: Relevance
“…However, no other study on COVID-19 has used the same tools. Knowledge of the causative agent and mortality rate of COVID-19 was low, and this corresponded with the findings of previous studies [ 24 ]. While previous studies have observed that the increase in the number of infectious diseases facilitates the need and opportunity to acquire knowledge [ 17 ], this study did not find any significant difference between the knowledge of residents from the Daegu and non-Daegu areas.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, no other study on COVID-19 has used the same tools. Knowledge of the causative agent and mortality rate of COVID-19 was low, and this corresponded with the findings of previous studies [ 24 ]. While previous studies have observed that the increase in the number of infectious diseases facilitates the need and opportunity to acquire knowledge [ 17 ], this study did not find any significant difference between the knowledge of residents from the Daegu and non-Daegu areas.…”
Section: Discussionsupporting
confidence: 89%
“…Nonetheless, studies have shown that individual awareness about the outbreak of an infectious disease is an essential factor that influences the implementation of preventive rules [ 14 , 21 , 22 , 23 , 24 ]. Individual awareness can be measured by examining one’s knowledge and attitude towards infectious diseases [ 14 , 23 , 25 ] or applying the health belief model [ 13 , 22 , 24 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In light of the above, it is important to provide the necessary mental health support [ 44 ]. We recommend the active and ongoing participation of mental health professionals in policy task forces during this critical period [ 45 ].To meet the needs of the general population during this pandemic, it is necessary to consider online or smartphone-based psychosocial education to promote mental health and psychological interventions [ 46 , 47 ], such as cognitive behavioral therapy (CBT) and mindfulness-based cognitive therapy (MBCT). MBCT focuses on the use of various mindfulness meditation exercises to develop a sense of right and wrong judgment and is particularly helpful in relieving stress in people with poor physical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of recommended preventive behavior during the COVID-19 pandemic include an empirical survey performed in China by Ye et al 25 that compared the adoption of basic, advanced, and excessive preventive behaviors in different groups of demographic characteristics. They found that predictors of proper preventive behavior include perceived sensitivity, perceived severity, perceived benefits, cues to action, and knowledge levels whereas predictors of excessive prevention behavior included perceived sensitivity and knowledge levels.…”
Section: Prevention Behaviors During the Covid-19 Pandemicmentioning
confidence: 99%